2013
DOI: 10.1007/978-3-642-38697-8_4
|View full text |Cite
|
Sign up to set email alerts
|

ω-Petri Nets

Abstract: We introduce ω-Petri nets (ωPN), an extension of plain Petri nets with ωlabeled input and output arcs, that is well-suited to analyse parametric concurrent systems with dynamic thread creation. Most techniques (such as the Karp and Miller tree or the Rackoff technique) that have been proposed in the setting of plain Petri nets do not apply directly to ωPN because ωPN define transition systems that have infinite branching. This motivates a thorough analysis of the computational aspects of ωPN. We show that an ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We introduce the, up to our knowledge, first formal model that grasps the core of Gcd, and that allows to derive basic results on the decidability of verification question thereupon. Due to the obvious undecidability issues of the model, we currently focus on several under-and over-approximative approaches (e.g., language bounded verification, graph minor based abstractions, novel Petri net extensions [12]) as well as enhancements for additional Gcd features like task groups, priorities, and timer events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We introduce the, up to our knowledge, first formal model that grasps the core of Gcd, and that allows to derive basic results on the decidability of verification question thereupon. Due to the obvious undecidability issues of the model, we currently focus on several under-and over-approximative approaches (e.g., language bounded verification, graph minor based abstractions, novel Petri net extensions [12]) as well as enhancements for additional Gcd features like task groups, priorities, and timer events.…”
Section: Discussionmentioning
confidence: 99%
“…Thus by extending the proof of Proposition 5: A terminates, then A is guaranteed to terminate. We have recently shown that the termination problem is decidable for Petri nets with ω-arcs [12]. Hence, also extended termination is decidable on the previous abstraction.…”
Section: Extending Qdas With Fork/joinmentioning
confidence: 94%
“…Formally, in an ω-PN, each transition is a pair t = (I t , O t ), where I t and O t are both functions from P to N ∪ {ω}. The semantics of O t ( p) = ω(I t ( p) = ω, respectively) is that the firing of t produces (consumes) a nondeterministically chosen, yet finite number of tokens in (from) p. The coverability and the termination problems are both decidable for ω-PN [Geeraerts et al 2013b].…”
Section: Overapproximations Of Eqdasmentioning
confidence: 98%
“…To recover a practical procedure for analyzing EQDAS, we propose using a recently introduced extension of Petri nets [Geeraerts et al 2013b], called ω-Petri net (ω-PN for short). ω-PN transitions with an arbitrary but fix number of tokens, and extends classical Petri nets by permitting arcs to be labeled by ω.…”
Section: Overapproximations Of Eqdasmentioning
confidence: 99%
“…However, WSTS such as inserting FIFO automata [7], inserting automata [6] and ω-Petri nets [17], that can arbitrarily increase some values, are intrinsically infinitely branching, and any finitely branching WSTS parameterized with an infinite set of initial states (such as broadcast protocols [10]) also inherits an infinitely branching state. For instance, Geeraerts, Heußner, Praveen and Raskin argue in [17] that parametric concurrent systems with dynamic Supported by the French Agence Nationale de la Recherche, REACHARD (grant ANR-11-BS02-001), by the Fonds québécois de la recherche sur la nature et les technologies, by the Natural Sciences and Engineering Research Council of Canada and by the "Chaire DIGITEO, ENS Cachan -École Polytechnique". thread creation can naturally be modelled by some classes of infinitely branching systems, like ω-Petri nets, i.e.…”
Section: Introductionmentioning
confidence: 99%